The Struktur Modal Terhadap Nilai Perusahaan Dengan Islamic Social Reporting (ISR) Sebagai Variabel Moderating - fransiska geby yosesia panggabean, fransiska geby yosesia panggabean (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2025)
This study aims to determine the effect of capital structure on firm value with Islamic Social Reporting (ISR) as a moderating variable in companies listed on the Jakarta Islamic Index (JII). The objects of this research are companies listed on the Jakarta Islamic Index (JII). The sampling technique used is purposive sampling. The data collection methods employed in this study are documentation and literature study methods. The data analysis method used in this research is moderated regression analysis (MRA) by operating SPSS software. The results of this study indicate that the capital structure variable has a positive and significant effect on firm value, Furthermore, the variable of capital structure, with Islamic Social Reporting as a moderating variable, has a negative and insignificant effect on firm value, indicating that Islamic Social Reporting cannot moderate firm value in companies listed on the Jakarta Islamic Index (JII). Time Period Limitations, the research time period carried out for 15 years, namely 2018-2023, is too short, so it is difficult to observe significant changes in capital structure and company value and it is recommended to extend the research period in order to observe more significant changes in capital structure and company value